Prospects for the use of artificial intelligence in dentistry - Doroshenko, О. М.; Bida, В. І.; Volosovets, Т. М.; Doroshenko, М. В.; Omelianenko, О. А.; Leonenko, П. В.; Doroshenko, М. М.; Andrusenko, А. С. (Actual Dentistry, 2024)
Introduction. In recent years, artificial intelligence (AI) has found widespread use in healthcare and dentistry, where it has increased the accuracy of diagnosis and clinical decision-making. However, artificial intelligence solutions have largely not entered everyday dental practice, mainly due to limited data availability, accessibility, structure and complexity, lack of methodological rigor and standards in their development, and practical questions regarding the value and utility of these solutions, but also ethics and liability. Any applicationof artificial intelligence in dentistry must demonstrate tangible value, such as improving access and quality of care, increasing efficiency and safety of services, empowering patients and supporting medical research, or increasing sustainability. Purpose: based on the analysis of literary sources, to determine the prospects and feasibility of implementing the use of artificial intelligence in dentistry. Materials and methods. Information search and analysis of scientific sources was carried out using scientometric databases Web of Science, PubMed, Google Scholar over the last 10 years. Conclusion. The next decade will show whether this time the expectations for real-world applications of artificial intelligence will be met, or whether we will once again face an “AI winter” that will bury hopes and enthusiasm. There are valid concerns about the protection and security of data and the transfer of important medical decisions to computers. At the same time, artificial intelligence has the potential to revolutionize the health care industry, including dentistry, by helping to address the shortcomings of traditional dental care, which have been heavily criticized. Keywords: dentistry, artificial intelligence, deep learning, diagnostics and clinical decision-making.